Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1164/ajrccm/148.3.606
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Narrowing and Closing Pressures in Patients with Obstructive Sleep Apnea

Abstract: Based on previous studies, we hypothesized that the pharynx collapses at multiple sites in most patients with obstructive sleep apnea (OSA). The purpose of this study was to document, in a population of apneic subjects, the site(s) of narrowing and closing pressure of the hypotonic pharynx. We endoscopically examined the pharynx in 45 OSA patients during sleep while they received nasal continuous positive airway pressure (CPAP), which produces hypotonia of pharyngeal muscles. Intrapharyngeal images and pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
1
8

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(132 citation statements)
references
References 14 publications
2
121
1
8
Order By: Relevance
“…Previous studies have confirmed that the velopharynx is the most common site of narrowing in the UA of OSA patients [20][21][22]. Therefore, the fact that mandibular advancement mechanically enlarges and improves velopharyngeal patency seems to be a reasonable concept [4,21].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that the velopharynx is the most common site of narrowing in the UA of OSA patients [20][21][22]. Therefore, the fact that mandibular advancement mechanically enlarges and improves velopharyngeal patency seems to be a reasonable concept [4,21].…”
Section: Discussionmentioning
confidence: 99%
“…Genioglossus activity has clearly been shown to be decreased during REM sleep (Sauerland & Harper, 1976;Sauerland et al 1981;Wiegand et al 1991) and it is conceivable that REM sleep is characterized by greater collapse in the oropharynx than the nasopharynx. However, this is speculative as all the previous studies on the site of upper airway narrowing in normal subjects and apnoeics have been performed during either NREM sleep or general anaesthesia (Isono et al , 1997Morrison et al 1993). …”
Section: Discussionmentioning
confidence: 99%
“…13,14,33 However, the use of a mouthpiece excludes the retropalatal region that is a common site of obstruction during sleep in patients with OSA. 34 In addition, a partial opening of the mouth is necessary for mouthpiece use. Mouth opening has been shown to increase upper airway collapsibility.…”
Section: Discussionmentioning
confidence: 99%